Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1007/s11276-014-0836-5
|View full text |Cite
|
Sign up to set email alerts
|

Exploring an energy-efficient DTN framework supporting disaster management services in post disaster relief operation

Abstract: In recent years, several investigations have been made on ''challenged network'' [also known as, delay tolerant network (DTN)] architectures highlighting their advantages and disadvantages. In spite of its inherent shortcomings of unreliability and delay, smart-phone based opportunistic network is gaining immense popularity in the research community due to its applicability in different adverse and extreme communication scenarios where traditional communication infrastructure is either unavailable or incapacit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Recently, Bhattachejee et al [65] compared different DTN routing protocols using different mobility models for post disaster relief operations; however, most of them are mobility models that are not specialized to disaster situations. Their results showed that MaxProp is the best performer in terms of overhead and delivery rate, and Spray and Wait is more efficient than MaxProp in terms of energy consumption.…”
Section: Delay Tolerant Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Bhattachejee et al [65] compared different DTN routing protocols using different mobility models for post disaster relief operations; however, most of them are mobility models that are not specialized to disaster situations. Their results showed that MaxProp is the best performer in terms of overhead and delivery rate, and Spray and Wait is more efficient than MaxProp in terms of energy consumption.…”
Section: Delay Tolerant Networkmentioning
confidence: 99%
“…For example, for MANETs routing protocols, DSR or AODV presents good performance results on well-connected scenarios [56] . On scenarios where battery is limited, DTNs protocols such as Spray and Wait, and PRoPHET are good alternatives [51,65] . Despite that DTN and MANET protocols seem to have similar communication standards, they were conceived differently.…”
Section: Communication Protocolsmentioning
confidence: 99%
“…Nodes can be pedestrians' mobile devices, on-board vehicle specialized devices, fixed relays, etc. In [5], the authors present a classification of these types of nodes, their mobility patterns, and communication abilities (terminals, stationary relays, dedicated fixed or mobile routing facilities, etc.) from the perspective of post-disaster communication and coverage.…”
Section: Disruption-tolerant Networkingmentioning
confidence: 99%
“…The use of MANET or DTN to deal with a crisis situation has already been proposed [20], [21]. Several studies have compared known protocols in a crisis scenario [5], [22]- [26], or the in everyday life [7], [27], [28]), and have shown the impact of mobility on system performance.…”
Section: B Mobility Modelsmentioning
confidence: 99%
See 1 more Smart Citation